Student’s Cognitive Engagement in Learning Process - Sesmiyanti Sesmiyanti (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
Students’ engagement becomes essential factors in learning process because students have to participate in learningprocess. Not only the students but also the teachers have to make a good atmosphere during classroom activities. They have to createlesson, assignment and also project that interested to the students. Students’ cognitive engagement involves the students to thinkduring academic task, they have to have motivated to improve their ability in learning and also they have to participate and active inthe classroom. This paper is literary study.